2005
DOI: 10.1002/kin.20067
|View full text |Cite
|
Sign up to set email alerts
|

Ethane oxidation and pyrolysis from 5 bar to 1000 bar: Experiments and simulation

Abstract: An extensive experimental study of ethane oxidation and pyrolysis has been conducted in the high pressure shock tube at UIC covering reflected shock pressures from 5-1000 bar, reaction temperatures up to 1550 K and stoichiometric ( = 1), fuel rich ( = 5), and pyrolytic mixtures. The experimental data has been used to develop a single model that can simulate the whole dataset very well and is the first ethane model capable of simulating experimental results over such an extensive range of pressure, temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The experimental work performed here at UIC has obtained data over a pressure range spanning 5 bar at the low end, which is close to the upper limit of most other chemical shock tubes, and up to 1000 bar at the high end, beyond the pressure capabilities of other chemical shock tubes. The experimental study of ethane combustion [29][30][31] spans P=5-1000 atm, T=1000-1500 K, oxidation (Φ=1, 5) and pyrolysis. Much of the higher pressure data 29,30 has been discussed in detail in prior DOE annual reports.…”
Section: (D) Ethane Combustionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental work performed here at UIC has obtained data over a pressure range spanning 5 bar at the low end, which is close to the upper limit of most other chemical shock tubes, and up to 1000 bar at the high end, beyond the pressure capabilities of other chemical shock tubes. The experimental study of ethane combustion [29][30][31] spans P=5-1000 atm, T=1000-1500 K, oxidation (Φ=1, 5) and pyrolysis. Much of the higher pressure data 29,30 has been discussed in detail in prior DOE annual reports.…”
Section: (D) Ethane Combustionmentioning
confidence: 99%
“…Much of the higher pressure data 29,30 has been discussed in detail in prior DOE annual reports. The experimental work in this annual period has been extended to pressures as low as 5 atm and the entire data set has been simulated with a single comprehensive chemical kinetic model 31 that can capture the experimental trends over the wide range of pressures, temperature and stoichiometry.…”
Section: (D) Ethane Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raghu et al [1] have performed calculations and experiments for CH 4 /C 2 H 6 /O 2 /NO flames under the conditions of equivalence ratio of 1.5 at pressure of 1.0 MPa in jet stirred reactor (JSR). In their calculations, the detailed mechanism proposed by Tranter et al [2] based on GRI-Mech 3.0 [3] was used. They reported that the experimental results for concentration profile in JSR were relatively good agreement with calculation.…”
Section: Introductionmentioning
confidence: 99%